How to draw cars like a pro - Taylor, Thom , 1955-; Hallett, Lisa (Saint Paul, Minnesota : Motorbooks, 2006)
If you've ever wanted to draw or design cars, this book is for you
1. A quick history of automobile design -- 2. Tools and equipment -- 3. Perspective -- 4. Proportion -- 5. Ellipses and axes -- 6. Sketching and line quality -- 7. Light source -- 8. Shadows and reflections -- 9. Technique -- 10. Color -- 11. Presentation -- 12. Cartoons -- 13. Cutaways -- 14. Interiors 122 -- 15. Computers -- 16. Schools
Includes index
Keywords: Automobiles in art; Drawing -- Technique